Adequate Models for Multiprocessor Stochastic Systems - Nadwa S. Younis (College of Education for Pure Sciences, 2012)
Abstract In this paper, two models are presented for Multiprocessor Stochastic Systems (MSS). The first one is the Generalized Semi-Markov Process (GSMP), the second is the Generalized Stochastic Petri Net (GSPN). These models are used to study performance arbitrary parameters of (MSS). Our main result is by constructing an isomorphism mapping between (MSS) model and (GSPN) model. This isomorphism captures the essential dynamical structure of (MSS).